Evaluation of the efficacy and safety of first- and second-line immunotherapy in patients with metastatic colorectal cancer: a systematic review and network meta-analysis based on randomized controlled trials - Chen, Kaiqi; Chen, Wei; Yue, Rui; Zhu, Danping; Cui, Shikui; Zhang, Xijian; Jin, Zhao; Xiao, Tong (Frontiers in Immunology, 2024)
Background: Multiple randomized controlled trials (RCTs) for metastatic colorectal cancer (mCRC) patients demonstrated immunotherapy's efficacy using immune checkpoint inhibitors (ICIs). The FDA has approved ICIs for specific mCRC subpopulations. However, direct comparisons of treatment options are limited, leaving the most effective ICI strategies undefined for microsatellite-stable (MSS) and microsatellite instability (MSI) subgroups in first- and second-line therapies. Our study used Bayesian network meta-analysis to identify optimal ICI strategies. Methods: We searched PubMed, EMBASE, Cochrane Library, and Web of Science from inception to August 2024, screening 875 studies and ultimately including seven. A systematic review and network meta-analysis were performed. Results: Our analysis of seven RCTs, involving 1,358 mCRC patients, compared first- and second-line immunotherapy regimens. Five initial treatments focused on MSS (three) and MSI (two) patients, and two secondary regimens targeted MSS patients. Among 1051 first-line and 307 second-line patients, ICIs showed varying clinical benefits compared to standard-of-care therapy. Nivolumab with ipilimumab notably improved progression-free survival (PFS) in MSI patients (HR=0.21; 95% CI, 0.13-0.34) with low adverse events (OR=0.33; 95% CI, 0.19-0.56). For MSS patients, Nivolumab plus standard-of-care (SOC) significantly improved PFS (HR=0.74; 95% CI, 0.53-1.02). In second-line MSS therapy, Atezolizumab plus SOC prolonged PFS (HR=0.66; 95% CI, 0.44-0.99). Conclusions: ICIs in first- and second-line mCRC treatments confer substantial benefits. Nivolumab with ipilimumab may be the most efficacious and well-tolerated first-line option for MSI patients, while Nivolumab plus SOC is preferable for MSS patients. For MSS second-line therapy, Atezolizumab plus SOC is effective in prolonging PFS. Other ICI regimens also show promise, informing future treatment guidelines and rationale for ICI selection in mCRC.